Cow Manure Biogas Stove Design with Burner and Blower Performance for Housing Needs Scale - Hurip Jayadi; Sujangi Sujangi; Beny Suyanto (Humanistic Network for Science and Technology (HNST), 2019)
Biogas is a renewable energy that is environmentally friendly, easy to obtain and can be updated. The technology is simple and the energy produced can be used technically, socially, and economically especially to solve energy problem in rural area. The purpose of this research was to produce a biogas stove performance with appropriate technology that can be utilized by the community. This experimental research method was designing biogas stoves with performance using 2 variations of blower (3 watt and 6 watt) and two burners that is 2 mm and 4 mm. To know the performance of biogas stove, a test is done, that is : Water boilling test. The dimension was the biogas stove, the body of the stove was made of zinc (9x38x70 cm) with two furnaces, Ø 0.5 mm iron tube distribution, 2 and 4 mm burners, 3 and 6 watt blowers, gas lighters. The results of water boilling test was stove power with fire hole Ø 2 mm blower 3 watt (0.446630 KW) and efficiency (60,54982%); fire hole Ø 2 mm blower 6 watt (0.705517 KW) and efficiency (55.86828%); fire hole Ø 4 mm blower3 watts (0.913373 KW) and efficiency (54.45203%); fire hole Ø 4 mm blower 6 watts (1.231190 KW) and efficiency (51.06681%). The performance of the biogas stove showed that the smaller the hole is Ø (2 mm), the smaller the power will be, and more efficient. The greater use of the blower (6 watts) was, the greater power will be but more inefficient. These stoves can be utilized by the community especially those with biogas. For more minimal performance, cheap, durable and easy to use needs further research. Keywords: biogas stove; digester; blower and burner